Challenges for the Adoption of the Sustainable Development Perspective in Polish Evaluation Studies - Bryła, Paweł (Problemy Ekorozwoju, 2013)
This paper aims to examine the extent to which the sustainable development (SD) perspective is integrated into Polish major evaluation projects and to discern the challenges for incorporating the SD approach in evaluation research and practice in general. It will also try to identify the methodological challenges related to the SD evaluation procedures in Poland. The paper will overview these issues on the basis of a complete database of evaluation reports concerning EU structural funds implementation in Poland as well as selected evaluation reports and expert opinions commissioned by the Polish Ministry for Regional Development. The adoption of the SD perspective in Polish evaluation studies is still virtually inexistent, despite some positive trends in the field of building the evaluation culture, which are supported by the requirements imposed by the European Union.